2016
DOI: 10.33549/physiolres.933121
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentrations and Subcutaneous Adipose Tissue mRNA Expression of Clusterin in Obesity and Type 2 Diabetes Mellitus: the Effect of Short-Term Hyperinsulinemia, Very-Low-Calorie Diet and Bariatric Surgery

Abstract: Clusterin is a heterodimeric glycoprotein with wide range of functions. To further explore its possible regulatory role in energy homeostasis and in adipose tissue, we measured plasma clusterin and its mRNA expression in subcutaneous adipose tissue (SCAT) of 15 healthy lean women, 15 obese women (OB) and 15 obese women with type 2 diabetes mellitus (T2DM) who underwent a 2-week very low-calorie diet (VLCD), 10 obese women without T2DM who underwent laparoscopic sleeve gastrectomy (LSG) and 8 patients with T2DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…In support of our results, previous studies by Won et al in 204 Korean adults also demonstrated higher clusterin levels in overweight/obese subjects than in lean subjects as well as a positive relationship between serum clusterin levels and BMI . Serum clusterin levels were significantly reduced after weight reduction in obese subjects who underwent very‐low‐calorie diet treatment . All these results suggest that obesity is a factor that influences clusterin levels.…”
Section: Discussionsupporting
confidence: 91%
“…In support of our results, previous studies by Won et al in 204 Korean adults also demonstrated higher clusterin levels in overweight/obese subjects than in lean subjects as well as a positive relationship between serum clusterin levels and BMI . Serum clusterin levels were significantly reduced after weight reduction in obese subjects who underwent very‐low‐calorie diet treatment . All these results suggest that obesity is a factor that influences clusterin levels.…”
Section: Discussionsupporting
confidence: 91%
“…Increased CLU levels are associated with T2DM, metabolic syndrome and cardiovascular diseases [44,45]. Kujiraoka et al [46] reported higher serum CLU levels in diabetes patients than in patients with myocardial infarction, chronic coronary artery disease, or diabetes combined with chronic coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…In the only study of AT CLU, a 2-week very-low-calorie diet reduced plasma clusterin levels, and whole fat clusterin mRNA decreased after sleeve gastrectomy (43). In obese subjects, plasma clusterin levels were elevated and positively associated with BMI, inflammation (hs-CRP and retinol-binding protein-4) (16), and IR (14).…”
Section: Discussionmentioning
confidence: 99%